Comparing presentations and outcomes of children with cancer: a study between a lower-middle-income country and a high-income country - Ahmed Farrag; Mohamed Hamdy Ghazaly; Khaled Mohammed; Ruth Volland; Barbara Hero; Frank Berthold (BMC, 2023)
Abstract Background Substantial progress has been achieved in managing childhood cancers in many high-income countries (HICs). In contrast, survival rates in lower-middle-income countries (LMICs) are less favorable. Here, we aimed to compare outcomes and associated factors between two large institutions; Egypt (LMIC) and Germany (HIC). Methods A retrospective review was conducted on newly diagnosed children with cancer between 2006 and 2010 in the departments of pediatric oncology at the South Egypt Cancer Institute (SECI) (n = 502) and the University Hospital of Cologne-Uniklinik Köln (UKK) (n = 238). Characteristics including age, sex, diagnosis, travel time from home to the cancer center, the time interval from initial symptoms to the start of treatment, treatment-related complications, compliance, and outcome were analyzed. A Cox proportional hazards regression model was applied to investigate the influence of risk factors. Results The most common diagnoses in SECI were leukemia (48.8%), lymphomas (24.1%), brain tumors (1%), and other solid tumors (24.7%), compared to 22.3%, 19.3%, 28.6%, and 26.5% in UKK, respectively. Patients from SECI were younger (5.2 vs. 9.0 years, P < 0.001), needed longer travel time to reach the treatment center (1.44 ± 0.07 vs. 0.53 ± 0.03 h, P < 0.001), received therapy earlier (7.53 ± 0.59 vs. 12.09 ± 1.01 days, P = 0.034), showed less compliance (85.1% vs. 97.1%, P < 0.001), and relapsed earlier (7 vs. 12 months, P = 0.008). Deaths in SECI were more frequent (47.4% vs. 18.1%) and caused mainly by infection (60% in SECI, 7% in UKK), while in UKK, they were primarily disease-related (79% in UKK, 27.7% in SECI). Differences in overall and event-free survival were observed for leukemias but not for non-Hodgkin lymphoma. Conclusions Outcome differences were associated with different causes of death and other less prominent factors.